A Study on Forming for Plate-Type Heat Exchangers of the Ti Material. (2017) - Jin, Byeong-Ju; Lee, Jong-Pyo; Park, Min-Ho; Yun, Tae-Jong; Song, Youg-Ho; Kim, Ill-Soo
Abstract: Generally, the heat transfer performance of plate-type heat exchanger has been shown lower than other heat exchangers. Recently titanium material that has high formability and performance has been payed attention to a plate material of the plate-type heat exchange. However, the material has a spring-back due to the high strength as well as the mold design for die and punch processes determined by the operator's experience. Furthermore, the factors that affect the sheet forming are too large and complex to describe by mathematical method so that it is quite difficult for the exact design by experimental methods. Since the chevron shape and pattern are important factors in the performance of the plate-type heat exchanger, the heat exchanger that has the same performance with the targeted one has been manufactured in conjunction with mold design. This design has been employed to predict and determine performance of plate-type heat exchanger. If the mold design of the plate-type heat exchanger has considered to the spring-back phenomenon, the design of two-dimensional shape should necessarily be required. Therefore, the compatibility and adequacy of mold design in the plate-type heat exchanger which is used in the industries, can be verified using three-dimensional(3D) Finite Element Method(FEM). In this paper, a forming analysis of a plate-type heat exchanger with its numerical simulation has been carried out. The optimization of mold design in plate-type heat exchanger that has the complex shape has been proposed using the computer simulation. Since the high-tensile steel plate such as Ti material has high stability when designing a metal mold in the new product, an optimization in the quality of plate-type heat exchanger using the developed numerical model has been proposed.